Prevalence of Lung Cancer in Non Smoker Patients Attending Al-Diwaniyah Teaching Hospital - Hassan Raji Jallab1, Thimar Malik Khudhair2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background: Smoking is a well known risk factor that is implicated in a number of human malignant disorders.Aim of the Study: To study the prevalence of lung cancer in a sample of Iraqi non smoker patients and the main risk factor implicated in such malignant tumor.Patients and Method: In this hospital based study, in order to explore the prevalence rate of bronchogenic carcinoma in non smoker patients ,it retrospectively collected data about those patients for the last four years, starting from January 2016 through June 2019. These information were retrieved from patients records that are already present in oncology and respiratory units in Al-Diwaniyah teaching hospital, Al-Diwaniyah province, Mid-Euphrates region of Iraq. The following variables were included in the questionnaire form: Age, gender, occupation, education level, residency, socioeconomic status, marital status history of smoking, history of second hand smoking, number of household smokers, type of smoking, history of alcoholism, history of chronic illness, the main presenting clinical features and clinical features of carcinoma and finding in examination as well as those obtained from investigations.Results: In the current study, the prevalence rate of all cases of lung cancer during the period of study was 61 out of 403 (15.1 %). the rate of lung cancer in none smokers, in the current study, was 39.3 %. Old age individuals were the main age group affected and there was female predilection. there was also no significant difference in the distribution of patients and control subjects according to residency, occupation, level of education marital status and socioeconomic status (P > 0.05). In the current study, the prevalence rate of passive smoking in patients was significantly higher than that in control subjects, 70.8 % versus 40 %. Moreover, the number of household smokers was significantly higher inpatients group than in control group.Conclusion: Lung cancer in non smokers appears to be significantly correlated with passive smoking in addition to increase incidence in old age and women.